APLIKASI METODE PEMBELAJARAN THE POWER OF TWO DALAM PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN AL-QUR’AN HADITS DI MTS BAHRUL ULUM BARENG JOMBANG - Binti Masrufa; Moch. Sya'roni Hasan (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2019)
The method is very important in learning. Madrasah Tsanawiyah Bahrul Ulum Together in learning the Koran using a unique method, the power of two, the method begins with the teacher giving questions to be answered independently by all students. Then divide students in heterogeneous pairs. Students are asked to give new answers to the results of discussions with their partners. Then all pairs compare their answers with the answers of other pairs. Finally the teacher concludes the most appropriate answer. This method is applied periodically and in certain materials so that students do not get bored. Student learning outcomes at MTs Bahrul Ulum have improved. The increase occurred in cognitive, affective, and psychomotor aspects. This is supported by the activeness of students expressing opinions, asking questions, responding, answering questions from other friends and applying it in their daily relationships. Improvements were also seen in the scores of daily tests and midterm scores of students. problems by students are: negative student dependence, lack of learning materials, and limited student memory. The solution to the problem that arises is: the teacher selectively divides couples heterogeneously, the teacher as the controller of the discussion, the addition of extracurricular hours in the religious field, assigns students who are passive to convey the results of discussions with their partners, asks students to look for material from other sources, and puts emphasis on main points of discussion.